2020
DOI: 10.1186/s12974-020-1718-7
|View full text |Cite
|
Sign up to set email alerts
|

Decreased expression of Rev-Erbα in the epileptic foci of temporal lobe epilepsy and activation of Rev-Erbα have anti-inflammatory and neuroprotective effects in the pilocarpine model

Abstract: Background: A hallmark of temporal lobe epilepsy (TLE) is brain inflammation accompanied by neuronal demise. Accumulating evidence demonstrates that Rev-Erbα is involved in regulating neuroinflammation and determining the fate of neurons. Therefore, we studied the expression and cellular distribution of Rev-Erbα in the epileptogenic zone of TLE and the effect of treatment with the Rev-Erbα specific agonist SR9009 in the pilocarpine model. Methods:The expression pattern of Rev-Erbα was investigated by western b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 46 publications
1
15
2
Order By: Relevance
“…However, in contrast to this study, Rev‐erbα was found to be reduced in the epileptic foci from temporal neocortex samples of patients with temporal lobe epilepsy 36 . This study also demonstrated that Rev‐erbα was decreased in the hippocampus and temporal neocortex of mice treated with pilocarpine both in the acute status epilepticus and the chronic phase 36 . Thus, there is evidence implicating Rev‐erbα in different models of epilepsy, albeit with varying results.…”
Section: Circadian Gene and Protein Expression In Epilepsycontrasting
confidence: 95%
See 2 more Smart Citations
“…However, in contrast to this study, Rev‐erbα was found to be reduced in the epileptic foci from temporal neocortex samples of patients with temporal lobe epilepsy 36 . This study also demonstrated that Rev‐erbα was decreased in the hippocampus and temporal neocortex of mice treated with pilocarpine both in the acute status epilepticus and the chronic phase 36 . Thus, there is evidence implicating Rev‐erbα in different models of epilepsy, albeit with varying results.…”
Section: Circadian Gene and Protein Expression In Epilepsycontrasting
confidence: 95%
“…Finally, in the aforementioned electroconvulsive study, Rev‐erbα showed the most significant change in its increase in gene oscillation pattern in line with an increase in steady‐state mRNA and protein levels in the frontal cortex of epileptic mice 26 . However, in contrast to this study, Rev‐erbα was found to be reduced in the epileptic foci from temporal neocortex samples of patients with temporal lobe epilepsy 36 . This study also demonstrated that Rev‐erbα was decreased in the hippocampus and temporal neocortex of mice treated with pilocarpine both in the acute status epilepticus and the chronic phase 36 .…”
Section: Circadian Gene and Protein Expression In Epilepsycontrasting
confidence: 71%
See 1 more Smart Citation
“…In addition to ERs, a PPAR β / δ agonist significantly reduces neuroinflammation after hypoxia–ischemia by inhibiting the expression of TXNIP and NLRP3 ( 134 ). Furthermore, temporal lobe epilepsy (TLE) is characterized by spontaneous recurrent seizures leading to neuroinflammation features such as astrocytosis associated with microglia activation and inflammatory cytokine production ( 156 ) ( Table 1 ). In the context of human and mouse TLE, the Rev-erb ligand, SR9009, prevents neuroinflammation by inhibiting NLRP3 mRNA and protein levels, reducing astrocytes and microglial activation and decreasing apoptosis, which then preserves neurons and provides neuroprotection ( 156 ).…”
Section: Regulatory Function Of Nr In Nlrp3-driven Diseases and Theirmentioning
confidence: 99%
“…Previous studies showed seizure activity led to the production of inflammatory molecules including IL-1β and TNF-α ( He et al, 2020 ). In turn, IL-1β or TNF-α could contribute to the severity and relapse of seizures ( Yue et al, 2020 ). Moreover, inhibition of IL-1β or TNF-α expression may lead to prevention or delay of seizures and play a neuroprotective effect on a rat model of temporal lobe epilepsy ( Noe et al, 2013 ; Sitges et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%